Kajian awal residu karbofuran di dalam ubi keledek / Harbant Singh, Muhammad Idris Salleh and Putri Ibrizah Zahariman - Singh, Harbant; Salleh, Muhammad Idris; Zahariman, Putri Ibrizah (1991)
The purpose of the present study was to identify the correct dosage of Furadan 3 G, a systemic insecticide, in the control of Cylas sp. in sweet potato (ubi keledek). Residue studies on carbofuran in the plant and soil were done. The residue of carbofuran in polybag soil was about 30 days. No carbofuran residue was detected in the tubers at various treatments of Furadan. Treatment T3 (1.5 Kg Furadan 3 G / ha) was considered to be the best dosage, since it was able to control the pest population by more than 80 %, besides showing a phytotonic effect on the formation of tubers. In the collaboration of the GC, carbofuran was successfully isolated from the commercial product of Furadan 3 G, using the solid phase extraction method, a modification of the methods of Beauchamp et al, 1989 and Getzin et_al, 1989.